1971
DOI: 10.1111/j.1365-2621.1971.tb03332.x
|View full text |Cite
|
Sign up to set email alerts
|

POULTRY PRODUCT QUALITY. 5. Microbiological Evaluation of Mechanically Deboned Poultry Meat

Abstract: SUMMARY —Samples of deboned meat from broiler necks and backs, whole fowl and turkey racks were obtained from commercial sources and examined for total aerobic counts, fecal coliforms, salmonellae, Clostridium perfringens, coagulase positive staphylococci and psychrotolerant microorganisms. The raw materials were either deboned immediately after birds were processed (conventional processing) or held in the plants at 3–5°C for 5 days prior to deboning (delayed processing). The storage studies were conducted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…As there are no interventions applied to swine or poultry bones or carcass parts that would reduce Salmonella contamination. It is therefore reasonable to conclude that pork and poultry MSM may also be contaminated with these bacteria as was demonstrated by Ostovar et al (1971) who reported 11% of poultry MSM to be Salmonella positive.…”
Section: Public Health Risks Linked To the Different Types Of Msmmentioning
confidence: 94%
See 2 more Smart Citations
“…As there are no interventions applied to swine or poultry bones or carcass parts that would reduce Salmonella contamination. It is therefore reasonable to conclude that pork and poultry MSM may also be contaminated with these bacteria as was demonstrated by Ostovar et al (1971) who reported 11% of poultry MSM to be Salmonella positive.…”
Section: Public Health Risks Linked To the Different Types Of Msmmentioning
confidence: 94%
“…Gomes et al (2003), while investigating the effect of gamma radiation on refrigerated poultry MSM, reported an increase in psychrotrophic TVC from approximately 3.8 log 10 cfu g -1 to 4.9 log 10 cfu g -1 after 4 days, to 6.6 log 10 cfu g -1 after 6 days and to 7.8 log 10 cfu g -1 after 8 days storage at 2°C. An earlier study by Ostovar et al (1971) had previously shown an increase in TVC from 3.35 x 10 5 cfu g -1 to 7.10 x 10 5 cfu g -1 on MSM derived from poultry immediately after slaughter as compared with MSM when the raw materials were stored at 3°C to 5°C for 3 to 5 days. In poultry MSM, TVC also increased from 3.25 x 10 5 cfu g -1 to 9.32 x 10 6 cfu g -1 after storage at 3°C for 12 days.…”
Section: Public Health Risks Linked To the Different Types Of Msmmentioning
confidence: 99%
See 1 more Smart Citation
“…Su 54 campioni esaminati, 6 contenevano salmonelle e 4 C. perfringens, ma in nessun caso è stato rinvenuto S. aureus 137 . La qualità microbiologica del pollame disossato è stata comparata con altri prodotti avicoli crudi: sebbene le conte siano risultate paragonabili, i valori MPN dei coliformi nei prodotti MDM commerciali variavano da 460 fino a oltre 1110/g.…”
Section: Carni Disossate Meccanicamenteunclassified
“…Bacteria such as Pseudomonas and Achromobacter, which have been identified in mechanically deboned poultry meat by Ostovark et al (1971), can attack and utilize certain carbonyl compounds (Smith and Alford, 1968). Moerck and Ball (1974) Depending upon the type of microflora present in meat tissue and growing conditions under which the meat is stored, either increases or decreases in pH can occur (Ockerman et al, 1969;Borton, 1969), and changes in pH influence the emulsifying capacity and emulsion stability of poultry meat (Hudspeth and May, 1967;Parkes and May, 1968;Froning and Neelakantan, 1971;McCready and Cunningham, 1971;Neelakantan and Froning, 1971).…”
Section: Microbiological Properties and Phmentioning
confidence: 99%